On the Issue of the Problems of Family Education - Reymov Mukhamedali Kengesbaevich; Zueva Arina Viktorovna (Genius Journals, 2021)
The article reviewed widespread problems of family education and their reasons. The author considers that family education is the process of parents-child cooperation, which leads to a formation of a definite evolutional level. The process of family education should be thoroughly realized and analyzed in order to make positive educational results.
Keywords: Family; education; child; personality